Propagation modelling and measurements for a microcellular communication system - Wong, Kee Boon. (2008)
This thesis presents results of experimental and theoretical studies of propagation characteristics in a micro-cellular communication system; such as power delay profile, signal path loss, and RMS delay spread in various indoor environments. A three-dimensional ray tracing propagation model based on the Uniform Theory of Diffraction (UTD) is developed to include all possible reflections and transmissions of signals from/through the scatterers and obstacles, as well as diffraction from the edges and corners.